In vivo pharmacokinetic evaluation of molnupiravir in patients with severe chronic kidney disease - Wang, Yuanyuan; Chen, Qiong; Liu, Xuan; Zhang, Ling; Chen, Ming; Wang, Shuowen; Yang, Man; Fan, Guorong; Fan, Qiuling (Frontiers in Pharmacology, 2025)
IntroductionMolnupiravir (MPV) is an oral, potent ribonucleoside analog that inhibits the replication of SARS-CoV-2 and is indicated for the treatment of adults with COVID-19. Patients with COVID-19 are at an elevated risk of adverse outcomes, underscoring the need for precise pharmacokinetic (PK) data to guide safe drug use. For MPV and its active metabolite, N4-hydroxycytidine (NHC), renal excretion is not the primary elimination pathway. Consequently, renal impairment has minimal impact on their PK profiles, and no dose adjustment is recommended for patients with mild to moderate renal impairment. However, there are no relevant pharmacokinetic studies in patients with severe renal insufficiency (eGFR<30 mL/min/1.73 m2) or patients requiring dialysis. This study aims to explore the plasma concentration of MPV in patients with severe renal insufficiency, providing a basis for rational clinical use of drugs.MethodsLiquid chromatography-tandem mass spectrometry (LC-MS/MS) was used to detect the plasma concentrations of MPV and NHC. All analytes were extracted by protein precipitation using acetonitrile at a ratio equivalent to 3:1, and QMPV and QNHC were evaluated by calculating the ratio of plasma concentrations.ResultsA total of four patients with stage 4 or 5 chronic kidney disease (CKD) were enrolled in the study. All patients received a standard oral dose of molnupiravir (MPV), and plasma samples were collected 12 h post-administration (C12h) for analysis. Plasma concentrations of MPV itself were consistently low at 12 h post-dose. In contrast, the 12-h plasma concentration of N4-hydroxycytidine (NHC, the active metabolite of MPV) in patients with severe renal insufficiency (stage 4/5 CKD) was significantly higher than that in reference populations: compared with healthy subjects (NHC C12h: 16.7 ng/mL) and patients with mild to moderate renal impairment (NHC C12h: 31.1 ng/mL), the NHC C12h in the severe renal insufficiency group ranged from 43 to 1,600 ng/mL. Notably, the patient with stage 5 CKD exhibited the highest NHC plasma concentration (1,600 ng/mL) at 12 h post-dose, which remained at a persistently elevated level.ConclusionMPV was rapidly hydrolyzed to NHC in the body and maintained at a low level. The NHC is significantly higher than that of patients with mild to moderate symptoms, especially those with stage 5 chronic kidney disease. The blood drug concentration is equivalent to Cmax, which suggests that when used clinically in patients with uremia, the dosing interval should be adjusted to avoid drug accumulation and occurrence of AEs.